Association of systemic inﬂammation response index with all-cause mortality as well as cardiovascular mortality in patients with chronic kidney disease - Wei, Lu; Mao, Shiqing; Liu, Xianhong; Zhu, Chuanqi (Frontiers in Cardiovascular Medicine, 2024)
Background: Chronic Kidney Disease (CKD) stands as a formidable health challenge, recognized not only for its growing prevalence but also for its association with elevated mortality rates. Emerging evidence suggests that CKD is inherently linked to inflammatory processes, marking it as an inflammatory disorder. In this landscape, the systemic inflammatory response index (SIRI) emerges as a novel inflammation marker, yet to be applied for assessing the risk of mortality in CKD patients.Objective: This study aims to investigate the prognostic significance of the SIRI in predicting all-cause and cardiovascular disease (CVD) mortality among patients with CKD.Method: This study conducted a retrospective observational study using the National Health and Nutrition Examination Survey (NHANES) database, encompassing data from 1999 to 2018. This analysis included 9,115 CKD patients, categorized based on SIRI quartiles. Key outcomes were all-cause and CVD mortality, analyzed using Kaplan-Meier survival curves, restricted cube splines (RCS) and cox proportional hazards models.In this study of 9,115 CKD patients, the Kaplan-Meier survival analysis revealed a greater incidence of all-cause death among groups with higher SIRI (P-log rank < 0.001). In the fully adjusted model (Model 3), each unit increase in SIRI led to a 20% increase in the risk of all-cause mortality. Additionally, higher SIRI quartiles (Q3 and Q4) were associated with increased risk compared to the lowest quartile (Q1) (Q3: